Changes in the public health infrastructure in Poland in the context of an aging population - Monika Pajewska; Olga Partyka; Katarzyna Kwiatkowska; Magdalena Krysińska; Joanna Bulira-Pawełczyk; Aleksandra Izabela Czerw (Kazimierz Wielki University, 2018)
The problem of an aging society, particularly the health situation of a group of older people is a challenge for health care for the coming years. Poland among other EU member states has one of the lowest (1) share of the population aged 65 years and older, they constitute approx. 17% of the population. Despite this, according to forecasts up to 2060 Polish society will be the oldest in Europe. Multidisease, polypharmacy and insufficient number of specialists is unfortunately characteristic of this group identify. This creates a need for a specific type of care that takes into account all aspects of the disease, integrating often use several different treatments at the same time. Among the population over 65 years of assistance in connection with, among others, dependence requires approx. 36%, and the proportion increases with age. It can be assumed estimates that the number of people in need of substantial assistance in complex activities of everyday life is 750 thousand. (2). In the system of care for older people play a crucial role alternative forms of care such as day care centers, senior clubs, the daily nursing homes. These institutions fulfill complementary function, ensuring the safety of patients not only medically, but also caring. In addition to providing health care infrastructure for the elderly it is essential to adequate saturation system with trained medical staff. According to the Polish Chamber of Physicians number of geriatricians authorized to practice the profession in Poland is amounted to 433 people in 2017, of which 422 were professionally active. Keep in mind that within one day it is impossible to create the base with geriatric specialists, which is why it is so critical to take action now.